UPAYA INDONESIA MENGEKSPOR SAGU KE MALAYSIA (STUDI KASUS: KABUPATEN KEPULAUAN MERANTI) - Annisa Sherlya Paiti; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study examines Indonesia's efforts to export sago to Malaysia in 2010-2016. The first time the two countries signed the Memorandum of Understanding in February 2009. The purpose of this cooperation is to strengthen, promote and develop bilateral cooperation between the two countries based on mutual benefits in the fields of food, horticulture, animal husbandry, agribusiness and other fields agreed by both parties. Malaysia's position adjacent to Indonesia provides an advantage for Indonesia. The easy transport links make the cost of production low so that the greater benefits are gained by both countries.This study uses a pluralism perspective which assumes that the state is not the only actor who plays a role in international relations, including in international trade transactions. As a directive in this study, the authors set the nation-state as the level of analysis in this study. In accordance with the fact that the main object of international relations is the nation-state. And the theory used in this study is the theory of comparative advantage. This research uses field research methods (Field Research) and research and literature (Library Research). Data in this research consist of primary data and secondary data. Primary data is done by interview and observation. Secondary data is obtained from a collection of readings, namely: books, documents, internet and other reading related to the issues discussed.The first time Indonesia cooperated with Malaysia on February 26, 2009 in Kuala Lumpur, the Indonesian and Malaysian parties held a Memorandum of Understanding (MoU). The Government of Indonesia is making efforts in which sago export activities can be run by improving the quality of sago in the external and internal fieldsKey words : Sago, Pluralism Perspective, Comparative Advantage